2019
DOI: 10.1093/jac/dkz299
|View full text |Cite
|
Sign up to set email alerts
|

Optimized meropenem dosage regimens using a pharmacokinetic/pharmacodynamic population approach in patients undergoing continuous venovenous haemodiafiltration with high-adsorbent membrane

Abstract: Background The pharmacokinetics (PK) of antibiotics change during sepsis and continuous renal replacement therapies in critically ill patients. Limited evidence exists on the use of the oXiris® high-adsorbent membrane. Objectives To develop a PK/pharmacodynamic (PD) model for meropenem in critically ill sepsis patients undergoing continuous venovenous haemodiafiltration (CVVHDF) with the oXiris® membrane, and to design an opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Nonlinear mixed-effects modelling has gained an important role in quantitative clinical pharmacology, drug development and therapeutic drug use [1,2]. In many applications when non-linear mixed effects modelling is employed, small datasets containing ten or even fewer subjects appear regularly [3][4][5], for example due to ethical concerns, high risks, high costs, low availability of patient (sub)groups of interest to the study or multiple factors. Conclusions drawn from such 'small-n' studies depend on the estimated parameters as well as parameter uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear mixed-effects modelling has gained an important role in quantitative clinical pharmacology, drug development and therapeutic drug use [1,2]. In many applications when non-linear mixed effects modelling is employed, small datasets containing ten or even fewer subjects appear regularly [3][4][5], for example due to ethical concerns, high risks, high costs, low availability of patient (sub)groups of interest to the study or multiple factors. Conclusions drawn from such 'small-n' studies depend on the estimated parameters as well as parameter uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, with the exception of the model proposed by Crandon et al, the pcVPC plots of most CRRT and non-CRRT models ( Roberts et al, 2009 ; Mattioli et al, 2016 ; Sjövall et al, 2018 ; Dhaese et al, 2019 ; Ehmann et al, 2019 ; Padullés Zamora et al, 2019 ; Grensemann et al, 2020 ; Onichimowski et al, 2020 ), displayed a remarkable trend in the overprediction of the typical population predictions and variability ( Supplementary Figure S1 ). The models by Burger et al (2018) and Jaruratanasirikul et al (2015) showed relative superiority in the pcVPC plot.…”
Section: Resultsmentioning
confidence: 71%
“…Among the models in the CRRT category and non-CRRT category, the Ulldemolins and Sjövall models displayed slight underestimations ( Ulldemolins et al, 2015 ; Sjövall et al, 2018 ), and the Onichimowski model ( Onichimowski et al, 2020 ) could be identified as a marginally better one, whereas rest ( Roberts et al, 2009 ; Mattioli et al, 2016 ; Dhaese et al, 2019 ; Ehmann et al, 2019 ; Padullés Zamora et al, 2019 ; Grensemann et al, 2020 ; Onichimowski et al, 2020 ) showed obvious overpredictions of meropenem concentrations ( Figure 2 ). Although none of the models showed compliance with the combined criteria of MDPE ≤ ±20%, MAPE ≤30%, F 20 ≥ 35%, and F 30 ≥ 50%, the models proposed by Muro et al (2011) , Crandon et al (2011) , and Burger et al (2018) ranked as the top three models with slightly preferable values of F 20 and F 30 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations